Public Awareness of Stroke and the Appropriate Responses in China: A Cross-Sectional Community-Based Study (FAST-RIGHT). Issue 2 (February 2019) - Li, Shengde; Cui, Li-Ying; Anderson, Craig; Zhu, Suiqiang; Xu, Ping; Wei, Tiemin; Luo, Yun; Chen, Shengli; Jiang, Nan; Hong, Yuehui; Liu, Weidong; Li, Jian; et al.
Abstract : Background and Purpose—: Early presentation is critical for receiving effective reperfusion therapy for acute ischemic stroke, therefore, we undertook a national survey of awareness and responses to acute stroke symptoms in China. Methods—: We undertook a cross-sectional community-based study of 187 723 adults (age ≥40 years) presenting to 69 administrative areas across China between January 2017 and May 2017 to determine the national stroke recognition rate and the correct action rate. Multivariable logistic regression models were used to identify factors associated with stroke recognition and intention-to-avail emergency medical services. Results—: Estimates of stroke recognition rate and correct action rate were 81.9% (153 675/187 723) and 60.9% (114 380/187 723), respectively, but these rates varied widely by sociodemographic status, region, and stroke risk. Approximately one-third of participants who recognized a stroke failed to call emergency medical service. Low likelihood of emergency medical service use was associated with younger age (40–59 years), being male, rural location, (regions of east, south, and northwest China), high body mass index (≥24), low education (primary school or below), low personal income (<US 731 per annum), living with immediate family, having multiple children (≥2), having a friend with stroke, exposure to less avenues to learn about stroke, nonsmoking, regular exercise, unknown family history, and no history of cardiovascular disease. Intention of calling emergency medical service was strongly related to awareness of stroke (odds ratio 2.05; 95% CI, 2.00–2.10; P <0.001). Conclusions—: Substantial discrepancies exist between stroke recognition and correct action and not all stroke patients know the appropriate responses. Further, national stroke educational programs with specific plans targeting different groups are needed, which do not solely focus on stroke recognition, but also on the appropriate responses at the time of a stroke. Abstract : Supplemental Digital Content is available in the text.